The precipitation behaviors, martensite transformation and superelasticity in the aged Ni-rich TiNi alloy with the assist of super-high stress. (January 2019) - Yi, Xiaoyang; Sun, Kuishan; Gao, Weihong; Wang, Haizhen; Sun, Bin; Yao, Wen; Meng, Xianglong; Gao, Zhiyong; Cai, Wei
Abstract: The precipitation of Ti3 Ni4 phase during aging under the assist of the super-high stress in the Ni-rich TiNi alloy was investigated. The Ti3 Ni4 precipitated in the matrix, accompanied by the generation of dislocations as a consequence of the applied super-high stress of several GPa level. The martensitic transformation behaviors changed from one-stage martensitic transformation to multiple-stage martensitic transformation with the changing of the applied stress level. The external applied super-high stress can result in the plastic deformation during aging, which can serve as the work hardening and further increase the micro-hardness, with an exception of the precipitation strengthening. In addition, the accumulation of larger numbers of dislocations and the generation of the localized stress field around the Ti3 Ni4 precipitate during aging due to the applied stress should be a certain responsible for the evolution of superelasticity strain. Graphical abstract: Highlights: The precipitation behaviors are investigated in aged Ni-rich TiNi alloy under the higher stress. The transformation path and temperatures are dependent on the applied stress level. Plastic deformation generates during aging owing to the applying of higher stress.